REFORMULASI STRUKTUR HUKUM YANG IDEAL BAGI LEMBAGA TINDAKAN PEMANANAN PERDAGANGAN (SAFEGUARDS) DI INDONESIA - Mahfud Fahrazi (Mimbar Hukum, 2021)
Abstract This research examines the Reformulation of the Ideal Legal Structure for Safeguards in Indonesia. The purpose of this study is to analyse the constraints on the effectiveness of Safeguards in Indonesia as well as reformulation of the ideal legal structure for Safeguards in Indonesia. This study uses a Normative type of research with a conceptual approach. The results of this study explain that the obstacles to the effectiveness of Safeguards in Indonesia are (1). The first drawback is that KPPI does not function as a tribunal institution, (2). Dependence with other institutions and (3). The existence of sectoral egoism. The reformulation of the ideal legal structure for Safeguards in Indonesia is to form an independent Indonesian trade remedy institute, which will function as a court or trade tribunal institution. In addition, it is also necessary to expand the authority of KPPI as a trade remedial agency which was initially limited to investigating serious losses or threats of serious loss and then added with the authority to make decisions on whether to determine import duties and coordinates which so far have been held by the Ministry of Trade and Finance. Intisari Penelitian ini mengkaji tentang Reformulasi Struktur Hukum yang ideal bagi Lembaga Tindakan Pengamanan Perdagangan (Safeguards) di Indonesia. Tujuan penelitian ini untuk menganalisis kendala efektivitas lembaga Tindakan Pengamanan Perdagangan (Safeguards) di Indonesia serta reformulasi struktur hukum yang ideal bagi lembaga Tindakan Pengamanan Perdagangan (Safeguards) di Indonesia. Kajian ini menggunakan jenis penelitian Normatif dengan pendekatan konseptual. Hasil penelitian ini menjelaskan bahwa kendala efektivitas lembaga Tindakan Pengamanan Perdagangan (Safeguards) di Indonesia yaitu adanya (1). Kelemahan pertama adalah Komite Pengamanan Perdagangan Indonesia (KPPI) tidak berfungsi sebagai lembaga tribunal. (2). Ketergantungan dengan lembaga yang lain serta (3). Adanya egoisme sektoral. Adapun reformulasi struktur hukum yang ideal bagi lembaga Tindakan Pengamanan Perdagangan (Safeguards) di Indonesia, yaitu dengan membentuk lembaga remedi perdagangan Indonesia yang independen, yang akan berfungsi sebagai institusi pengadilan atau tribunal perdagangan. Selain itu juga diperlukan adanya perluasan kewenangan KPPI sebagai lembaga remedi perdagangan yang awalnya hanya sebatas penyelidikan terhadap kerugian serius atau ancaman kerugian serius kemudian ditambah dengan kewenangan melakukan putusan apakah dilakukan penetapan bea masuk dan kuota yang selama ini dipegang kewenangannya oleh kementerian perdagangan dan keuangan.